Pengaruh Kualitas Pesan, Daya Tarik, Frekuensi Penayangan, Iklan Televisi Indomie - Ahmad Syarif, Handi, Ahmad Mardalis, SE.,MBA (2016)
This study aimed to examine the effect of the message quality, attractiveness, frequency of advertising on ad effectiveness Indomie both prasial and simultan.Sampel in this study were students of Muhammadiyah University of Surakarta amounting to 90 respondents. The sampling technique preformance this research is purposive sampling and non-sampling probabilty. The analytical method in gunaakan is normality test and multiple linear regression analysis test, t test, F test, and the coefficient of determination (R^2). In this study the data meet the normal distribution. Hypothesis tests showed that the quality of the message, appeal and frequency penyangan significantly influence the effectiveness of advertising with t_(arithmetic),each for 2,507, 3,021 and 2,006. In the F test showed that together the variable quality of the ad, attractiveness and frequency views significantly influence the effectiveness of ads. Results coefficient of determination(R^2)32.2%